Access to Quaternary Care Surgery: Implications for Accountable Care Organizations - Mehaffey, J Hunter (J Am Coll Surg, 2016)
BACKGROUND: Accountable Care Organizations (ACO) attempt to provide the most efficient and effective care to patients within a region. We hypothesize that patients who undergo surgery closer to home have improved survival due to proximity of preoperative and post-discharge care. STUDY DESIGN: All (17,582) institutional American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP) patients with a documented zip code and predicted risk who underwent surgery at our institution (2005–2014) were evaluated. Travel times were calculated by Google Maps, and patients were stratified by 1 hour of travel (local vs regional). Multivariable logistic regression and Cox Proportional Hazard models were used to evaluate the NSQIP risk-adjusted effects of travel time on operative morbidity, mortality, and long-term survival. RESULTS: Median travel time was 65 minutes with regional patients demonstrating significantly higher rates of ascites, hypertension, diabetes, disseminated cancer, >10% weight-loss, higher ASA, higher predicted risk of morbidity and mortality and lower functional status (all p<0.01). After adjusting for ACS NSQIP predicted risk, travel time was not significantly associated with 30-day mortality (OR 1.06, p=0.42) or any major morbidities (all p>0.05). However, survival analysis demonstrated travel time is an independent predictor of long-term mortality (OR 1.24, p<0.001) CONCLUSIONS: Patients traveling farther for care at a quaternary center had higher rates of comorbidities and predicted risk of complications. Additionally, travel time predicts risk-adjusted long-term mortality, suggesting a major focus of ACOs will need to be integration of care at the periphery of their region.